SEWA MENYEWA (IJARAH) DALAM SISTEM PERBANKAN SYARIAH - Rosita Tehuayo (TAHKIM, 2018)
Rental transactions in the conventional banking there is no property right transfer, meaning that if the lease term ends, the item is returned to the owner of the leasing object leases that generally does not require the services of a financial institution. Another case in practice because of known Islamic banking financing based on lease agreement - so-called Ijarah lease. In Islamic banking, al-Ijarah divided into 2 types namely: mutlaqah Ijarah or leasing, operating lease is a process that we usually encounter in daily economic activity. In the context of Islamic banking, Ijarah is a lease contract in which a bank or financial institution renting equipment (equipment), a building or goods, to one of its customers by charging fees that have been determined with certainty in advance. While al-Ijarah Al-Muntahia bit-Tamlik is a kind of fusion between the contracts of sale and lease or rental contract rather that ends with ownership of the goods in the hands of the tenant. The nature of transfer of ownership was also distinguishes it from ordinary lease, contained in conventional financial institutions. Al-Ijarah concept in Islamic banking as the lease in general, but what sets it apart is that in Islamic banking there is a lease which at the end of the contract, given the choice/option to customers to have the goods or not, commonly referred to leases purchase.